RCC2 Expression Stimulates ER-Positive Breast Tumorigenesis. (23rd May 2020) - Wang, Weiqi; Xu, Bing; Zhang, Zhaoxu; Fang, Kehua; Chang, Xiaotian
Abstract : Objective . Regulator of chromosome condensation 2 (RCC2) has been reported to be involved in the regulation of cell cleavage. This study investigated the effect of RCC2 expression on breast tumorigenesis. Methods . MCF-7 cells originating from estrogen receptor-positive (ER+) breast cancer were transfected with anti-RCC2 siRNA or RCC2-expressing plasmids. Cell proliferation, apoptosis, migration, and cytokine production in the transfected cells were examined using the CCK-8 assay, wound healing assay, and flow cytometry, respectively. PCR array was used to investigate the tumorigenic pathway of RCC2 in MCF-7 cells transfected with the anti-RCC2 siRNA. MCF-7 cells were also transfected with lentivirus-containing anti-RCC2 short hairpin RNA and were injected into BALB/c nude mice to generate tumor-bearing mice. Tumor growth in the mouse model was examined using magnetic resonance imaging by diffusion-weighted imaging analysis. Results . Western blotting and immunohistochemistry detected significantly increased expression of RCC2 in ER + breast tumor tissues compared with breast fibroadenoma samples. Inhibiting RCC2 expression decreased cell migration and stimulated apoptosis in MCF-7 cells, while overexpressing RCC2 stimulated cell migration and inhibited apoptosis. The inhibition of RCC2 expression significantly decreased breast tumor growth and IL-6 levels in the tumor-bearing mice. PCR array demonstrated that inhibiting RCC2 expression significantly decreased the expression of IGF1 and TWIST1, two well-known tumor-enhancing genes, in MCF-7 cells; conversely, overexpressing RCC2 increased the expression levels of these two genes in the transfected cells. This result was verified in the mouse model following inhibition of RCC2 expression in MCF-7 cells. Additionally, estradiol-17 β suppressed MCF-7 cell apoptosis, stimulated cell proliferation and cell migration, and increased RCC2, IGF1, and TWIST1 expression. The siRNA-mediated inhibition of RCC2 expression alleviated the inhibitory effects of estrogen on apoptosis in MCF-7 cells, while overexpressing RCC2 enhanced the estrogen-driven inhibition of apoptosis. Modifying RCC2 expression had no impact on MCF-7 cell proliferation in the presence or absence of estradiol-17 β . Conclusions . Our results suggest that estrogen-induced RCC2 expression prompts IGF1, TWIST1, and IL-6 expression, stimulates cell migration, and inhibits apoptosis to contribute to ER + breast tumorigenesis.